Bugs.jar: a large-scale, diverse dataset of real-world Java bugs - Saha, Ripon K.; Lyu, Yingjun; Lam, Wing; Yoshida, Hiroaki; Prasad, Mukul R. (2018 IEEE/ACM 15th International Conference on Mining Software Repositories (MSR), 2018)
We present Bugs.jar, a large-scale dataset for research in automated debugging, patching, and testing of Java programs. Bugs.jar is comprised of 1,158 bugs and patches, drawn from 8 large, popular open-source Java projects, spanning 8 diverse and prominent application categories. It is an order of magnitude larger than Defects4J, the only other dataset in its class. We discuss the methodology used for constructing Bugs.jar, the representation of the dataset, several use-cases, and an illustration of three of the use-cases through the application of 3 specific tools on Bugs.jar, namely our own tool, Elixir, and two third-party tools, Ekstazi and JaCoCo.